HUBUNGAN KADAR LEUKOSIT DENGAN LAMA RAWAT INAP PASIEN KEJANG DEMAM DI RSUD ULIN BANJARMASIN - Imanto, Talitha Natasya; Hidayah, Nurul; Huldani, Huldani (Homeostasis, 2023)
Febrile seizures are seizures that occur due to fever, which is thought to be associated with an increase in leukocytes and can be associated with length of hospitalization. This study aims to assess the relationship between leukocyte levels and length of hospitalization of patients with febrile seizures at Ulin General Hospital, Banjarmasin. The research was conducted using a Cross Sectional Study with a total of 60 samples. The sampling technique was carried out by purposive sampling method. The data is in the form of secondary data taken from medical records at Ulin General Hospital, Banjarmasin. Data analysis used chi-square (R2). The results showed normal leukocytes (78.3%), increased leukocytes (21.7%), hospitalization for ≤3 days (60%), and hospitalization for >3 days (40%). The results of the data analysis showed that there was no significant relationship (p=0.159) between leukocyte levels and the length of stay of patients with febrile seizures.